Impacto de las prácticas de cartelización de mercado en la competitividad de las organizaciones. Estudio de casos colombianos (2020)
This research established as objective the evaluation of the impact of market cartelization practices on the competitiveness of the organizations investigated by the Superintendencia de Industria Comercio (SIC) during the period 2014-2016. The methodology used in the development of this research responds to the analysis of qualitative content, through the Revision and categorization of information which was made based on a set of previously defined categories and according to the question posed. Among the main results, the theoretical and methodological elements on which business competitiveness is based were identified. In a second phase, the restrictive free competition practices detailed in the motivated reports and resolutions issued by the competent (SIC) entity were determined, with the intention of creating a balance on the type of behavior, the markets that were possibly affected. In the final phase, the possible effects of collusive practices on the competitiveness of these organizations are established.